The Role of Branched-Chain Amino Acids and Branched-Chain α-Keto Acid Dehydrogenase Kinase in Metabolic Disorders - Du, Chuang; Liu, Wen-Jie; Yang, Jing; Zhao, Shan-Shan; Liu, Hui-Xin (Frontiers in Nutrition, 2022)
Branched-chain amino acids (BCAAs), composed of leucine, isoleucine and valine, are important essential amino acids in human physiology. Decades of studies have revealed their role in protein synthesis, regulating neurotransmitter synthesis and mechanistic target of rapamycin (mTOR). BCAAs are found to be related to many metabolic disorders, such as insulin resistance, obesity, heart failure. Also, many diseases are related to the alteration of the BCAA catabolism enzyme branched-chain α-keto acid dehydrogenase kinase (BCKDK), including maple syrup urine disease, human autism with epilepsy and so on. In this review, diseases and the corresponding therapies are discussed after the introduction of the catabolism and detection method of BCAAs and BCKDK. Also, the interaction between microbiota and BCAAs is highlighted.